Adrenal venous sampling criteria for chemiluminescent enzyme immunoassay as a preferable alternative to radioimmunoassay in primary aldosteronism - Kazuki Nakai; Yuya Tsurutani; Koki Irie; Kyoko Teruyama; Sachiko Suematsu; Seishi Matsui; Kohzoh Makita; Jun Saito; Masao Omura; Tetsuo Nishikawa (Endocrine Journal)
Plasma aldosterone concentration (PAC) was routinely measured using radioimmunoassay (RIA); however, the RIA kit was discontinued in March 2021 in Japan. This study examined PAC conversion in adrenal venous sampling (AVS) and AVS criteria when measured using chemiluminescent enzyme immunoassay (CLEIA). PAC of 415 adrenal venous blood samples from AVS (including segmental AVS) of 63 patients with primary aldosteronism was measured using RIA (Spac-S aldosterone kit; Fujirebio Inc.) and CLEIA (Lumipulse Presto Aldosterone; Fujirebio Inc.). PAC of 70 AVS samples was also measured using liquid chromatography-mass spectrometry (LC-MS/MS, ASKA Pharma Medical Co., Ltd.). PAC conversion formulas were determined for each AVS sample assay. PAC measured using CLEIA was significantly correlated with that measured using RIA (correlation coefficient = 0.971). The PAC conversion formula was PAC (CLEIA) = PAC (RIA) × 0.772 – 1,199 pg/mL. The PAC of 14,000 pg/mL in RIA was equivalent to 9,613 pg/mL in CLEIA. PAC measured using CLEIA was also correlated with that measured using LC-MS/MS, and the PAC conversion formula was PAC (CLEIA, pg/mL) = 0.97 × PAC (LC-MS/MS, pg/mL) + 211. The inter-assay coefficient of variability (CV) was 1.1–1.3% and intra-assay CV was 1.0–1.7%, measured using CLEIA. The PAC conversion formula for AVS samples was obtained using CLEIA and RIA, and the conversion formula was different from that for peripheral blood. PAC values measured by CLEIA showed preferable accuracy and high concordance with those measured by LC-MS/MS, even in AVS samples. The study outcomes are useful for interpreting AVS results using non-RIA measurement methods.